Immune checkpoint inhibitors for recurrent endometrial cancer. Issue 3 (4th March 2022) - Mutlu, Levent; Harold, Justin; Tymon-Rosario, Joan; Santin, Alessandro D.
ABSTRACT: Introduction: Endometrial cancer (EC) is the most common gynecologic malignancy. Outcomes for patients with advanced and/or recurrent disease have been modest with the use of chemotherapy. The approval of immune checkpoint inhibitors targeting PD-1 has recently revolutionized human cancer treatment. Recent trials with immune checkpoint inhibitors used alone or in combination with other agents, have demonstrated remarkable efficacy in the treatment of the all-comers EC patient population. Areas covered: In this article, we review major clinical trials on PD-1/PD-L1 inhibitors in advanced and recurrent EC and discuss the response rates of these agents in the context of their genomic background. Expert opinion: Immune checkpoint inhibitors have significantly changed our approach to the treatment of advanced/recurrent EC. Single agent anti-PD-1 regimens are highly effective in MMRd/MSI-H patients, but their clinical efficacy remains modest in MMR proficient/TMB low EC patients. Combination regimens that can decrease the tumor microenvironments immunosuppression and increase tumor immunogenicity represent a viable treatment option to broaden the activity of immune checkpoint inhibitors in advanced/recurrent EC patients. An increased understanding of the biomarkers of response and the molecular mechanisms of resistance to immune checkpoint inhibitors remains key for the next advancement of the field.